2022
DOI: 10.1142/s0219843622400035
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Intelligent Substation Inspection Robot by Using Mobile Data

Abstract: Substation equipment inspection is essential for the power industry. The expansion of the smart grid scale improves the transmission capacity and enhances the likelihood of power plant facilities failure. To ensure the safety of the electric power supply, it is essential to inspect substation equipment. Metal commercial equipment can be traversed by remote inspection robots equipped with magnetic wheels. It is possible to use robots like this to examine equipment and pipelines remotely. In many cases, these ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They proposed a server deployment strategy based on machine learning in 6G IOT environment and confirmed that optimizing edge deployment also has good improvements. In the research of Qin et al, 11 a mobile-based Intelligent Tracking Framework (MITF) using inspection robots was developed to inspect substation equipments. In the MITF, a robot is integrated with a camera and thermal infrared imager sensors that have been collectively designated as workload.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They proposed a server deployment strategy based on machine learning in 6G IOT environment and confirmed that optimizing edge deployment also has good improvements. In the research of Qin et al, 11 a mobile-based Intelligent Tracking Framework (MITF) using inspection robots was developed to inspect substation equipments. In the MITF, a robot is integrated with a camera and thermal infrared imager sensors that have been collectively designated as workload.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature [19] attempted to train the resistance fault measurement method in a neural network and found that the optimized fault detection method can effectively solve the problem of detection failure due to the absence of accessible nodes and the abnormality of some input data. Literature [20] envisioned a mobile power fault detection and analysis framework with artificial intelligence technology as the underlying architecture for power facility inspection and fault detection, which effectively improves the safety and stability of substations. Literature [21] conceptualized a non-contact electrical engineering diagnostic model with infrared thermal imaging technology as the core logic, which has the advantages of high detection efficiency, low cost, and high detection accuracy.…”
Section: Introductionmentioning
confidence: 99%